Is it the 'same' result : replication in physics - Franklin, Allan, 1938- (IOP (Series). Release 5., 2018)
Replication, the independent confirmation of experimental results and conclusions, is regarded as the 'gold standard' in science. This book examines the question of successful or failed replications and demonstrates that that question is not always easy to answer. It presents clear examples of successful replications, the discoveries of the Higgs boson and of gravity waves. Failed replications include early experiments on the Fifth Force, a proposed modification of Newton's Law of universal gravitation, and the measurements of 'G', the constant in that law. Other case studies illustrate some of the difficulties and complexities in deciding whether a replication is successful or failed. It also discusses how that question has been answered. These studies include the 'discovery' of the pentaquark in the early 2000s and the continuing search for neutrinoless double beta decay. It argues that although successful replication is the goal of scientific experimentation, it is not always easily achieved.